Research

# A sharpened version of Hardy’s inequality for parameter p = 5 / 4

Yongping Deng1, Shanhe Wu1* and Deng He2

Author Affiliations

1 Department of Mathematics and Computer Science, Longyan University, Longyan, Fujian, 364012, P.R. China

2 Gangtou Middle School, Fuqing, Fujian, 350317, P.R. China

For all author emails, please log on.

Journal of Inequalities and Applications 2013, 2013:63  doi:10.1186/1029-242X-2013-63

 Received: 10 December 2012 Accepted: 1 February 2013 Published: 20 February 2013

This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

### Abstract

The purpose of this paper is to investigate a sharpened version of Hardy’s inequality for parameter p = 5 / 4 . By evaluating the weight coefficient W ( k , 5 / 4 ) , sharpened Hardy’s inequality that contains the best coefficient η 5 / 4 = 0.46 is established.

MSC: 26D15, 26D20, 26D07.

##### Keywords:
Hardy’s inequality; weight coefficient; sharpened inequality; exponential parameter; best coefficient

### 1 Introduction

Let p > 1 , 1 / p + 1 / q = 1 , a n 0 ( n = 1 , 2 , ), 0 < n = 1 a n p < . Then

n = 1 ( 1 n k = 1 n a k ) p < q p n = 1 a n p , (1)

where q p = ( p p 1 ) p is the best coefficient. Inequality (1) is called Hardy’s inequality which is of great use in the field of modern mathematics (see [1,2]).

A special case of (1) yields the following inequalities:

n = 1 ( 1 n k = 1 n a k ) 2 < 4 n = 1 a n 2 , (2)

n = 1 ( 1 n k = 1 n a k ) 3 < 27 8 n = 1 a n 3 . (3)

In 1998, Yang and Zhu [3] evaluated the weight coefficient W ( k , p ) ,

W ( k , p ) = k 1 1 / p n = k 1 n p ( j = 1 n 1 j 1 / p ) p 1 , k = 1 , 2 , , (4)

and established an improved version of inequality (2) as follows:

n = 1 ( 1 n k = 1 n a k ) 2 < 4 n = 1 ( 1 1 3 n + 5 ) a n 2 . (5)

With the same approach, that is, evaluating the weight coefficient W ( k , p ) , Huang [4-7] gave some improvements on Hardy’s inequality for p = 3 and p = 3 / 2 , i.e.,

n = 1 ( 1 n k = 1 n a k ) 3 < 27 8 n = 1 ( 1 3 19 n 2 / 3 ) a n 3 , (6)

n = 1 ( 1 n k = 1 n a k ) 3 / 2 3 3 n = 1 ( 1 1 5 1 n 3 + 3 ) a n 3 / 2 . (7)

Some further extensions of Hardy’s inequality related to the range of parameter p were given in Huang [7,8].

In 2005, Yang [9] proved an inequality for the weight coefficient W ( k , 2 )

W ( k , 2 ) = k n = k 1 n 2 ( j = 1 n 1 j ) 4 [ 1 1 k ( 1 1 4 W ( 1 , 2 ) ) ]

and established the following inequality:

n = 1 ( 1 n k = 1 n a k ) 2 < 4 n = 1 ( 1 θ 2 n ) a n 2 , (8)

where θ 2 = 1 1 4 W ( 1 , 2 ) = 0.13788928 is the best coefficient under the weight coefficient W ( k , 2 ) .

In 2009, Zhang and Xu made use of the monotonicity theorem [10-13] and obtained an improvement of inequality (1):

n = 1 ( 1 n k = 1 n a k ) p ( p p 1 ) p n = 1 ( 1 c p 2 ( n 1 / 2 ) 1 1 / p ) a n p , (9)

where

c p = { ( p 1 ) [ 1 2 1 / p ( 1 1 / p ) ] , 1 < p 2 , 1 2 1 1 / p ( 1 1 / p ) p 1 , p > 2 .

By evaluating the weight coefficient W ( k , p ) , and with the help of an inequality-proving package called BOTTEMA [14,15], He [16] investigated a sharpened version of Hardy’s inequality for p N and obtained the following improved version of inequality (3):

n = 1 ( 1 n k = 1 n a k ) 3 27 8 n = 1 ( 1 θ 3 n 2 / 3 ) a n 3 , (10)

where θ 3 = 1 8 27 W ( 1 , 3 ) = 0.1673 is the best coefficient under the weight coefficient W ( k , 3 ) .

In addition, in [16] the author wrote the computer program HDISCOVER to accomplish the automated verification of the following inequality for p N (N is the set of natural numbers):

n = 1 ( 1 n k = 1 n a k ) p ( p p 1 ) p n = 1 ( 1 θ p ( 1 ) n 1 1 / p ) a n p , (11)

where θ p ( 1 ) = 1 ( p 1 p ) p W ( 1 , p ) is the best coefficient of (11) under the weight coefficient W ( k , p ) .

Recently, based on the program HDISCOVER 2012 written by Deng, He and Wu [17], an automated verification of inequality (11) is achieved for p Q (Qis the set of rational numbers).

For more detailed information of Hardy’s inequality, we refer the interested readers to relevant research papers [10,12,18-23].

In this paper, by evaluating the weight coefficient W ( k , 5 / 4 ) , we establish an improvement of Hardy’s inequality for parameter p = 5 / 4 as follows:

n = 1 ( 1 n k = 1 n a k ) 5 / 4 5 5 / 4 n = 1 ( 1 1 10 1 n 1 / 5 + η 5 / 4 ) a n 5 / 4 , (12)

where η 5 / 4 = 5 5 / 4 10 [ 5 5 / 4 W ( 1 , 5 / 4 ) ] 1 = 0.46 is the best coefficient under the weight coefficient W ( k , 5 / 4 ) .

### 2 Lemmas

To prove the main results in Section 3, we will use the following lemmas.

Lemma 1 (see[22])

If p > 1 , then for all integers n 1 , it holds that

p p 1 n 1 1 / p p p 1 + 1 2 + 1 2 n 1 / p j = 1 n 1 j 1 / p p p 1 n 1 1 / p p p 1 + 1 2 + 1 2 n 1 / p + 1 12 p 1 12 p n 1 + 1 / p . (13)

Lemma 2 (see[3])

If p > 1 , then for all integers n k 1 , it holds that

1 ( p 1 ) k p 1 + 1 2 k p < n = k 1 n p < 1 ( p 1 ) k p 1 + 1 2 k p + p 12 k p + 1 .

Lemma 3Let p > 1 , 1 / p + 1 / q = 1 , and let g r , g l be the functions defined by

g r ( x ) = 6 p + 12 q 1 12 p q x 1 / q + 1 2 q x 1 12 p q x 2 , g l ( x ) = p + 2 q 2 p q x 1 / q + 1 2 q x , x [ 1 , + ) .

Then 1 < g r ( x ) < 0 , 1 < g l ( x ) < 0 .

Proof Since p > 1 , 1 / p + 1 / q = 1 , hence 1 / x 1 + 1 / p 1 / x 2 for x [ 1 , + ) .

Further, we have

g r ( x ) = 6 p + 12 q 1 12 p q 2 x 1 + 1 / q 1 2 q x 2 + 1 6 p q x 3 6 p + 12 q 1 12 p q 2 x 2 1 2 q x 2 + 1 6 p q x 3 = ( 5 p x + x + 2 p ) ( p 1 ) 12 p 3 x 3 > 0 ,

and consequently, g r is strictly increasing on [ 1 , + ) .

Now, from g r ( 1 ) = 1 / p > 1 and lim x + g r ( x ) = 0 , it follows that g r ( x ) g r ( 1 ) = 1 / p > 1 and g r ( x ) < 0 .

Similarly, from

g l ( x ) = p + 2 q 2 p q 2 x 1 + 1 / q 1 2 q x 2 p + 2 q 2 p q 2 x 2 1 2 q x 2 = p 1 2 p 2 x 2 > 0 , g l ( 1 ) = 1 / p > 1 and lim x + g l ( x ) = 0 ,

we deduce that 1 < g l ( x ) < 0 .

Lemma 3 is proved. □

Lemma 4Let 1 < g ( x ) < 0 . If α ( 0 , 1 ] , then

( 1 + g ( x ) ) ( 1 + ( α 1 ) g ( x ) + ( α 1 ) ( α 2 ) 2 g 2 ( x ) ) ( 1 + g ( x ) ) α 1 + α g ( x ) + α ( α 1 ) 2 g 2 ( x ) .

If α [ 1 , 2 ] , then

( 1 + g ( x ) ) α 1 + α g ( x ) + α ( α 1 ) 2 g 2 ( x ) .

Proof When α ( 0 , 1 ] . By using the Maclaurin formula

( 1 + g ( x ) ) α = 1 + α g ( x ) + α ( α 1 ) 2 g 2 ( x ) + α ( α 1 ) ( α 2 ) ( 1 + θ g ( x ) ) α 3 6 g 3 ( x ) , θ ( 0 , 1 ) ,

and noticing 1 < g ( x ) < 0 , we find

1 + θ g ( x ) > 1 + g ( x ) > 0 , α ( α 1 ) ( α 2 ) ( 1 + θ g ( x ) ) α 3 6 g 3 ( x ) 0 , ( α 1 ) ( α 2 ) ( α 3 ) ( 1 + θ g ( x ) ) α 4 6 g 3 ( x ) 0 .

Thus

( 1 + g ( x ) ) α 1 + α g ( x ) + α ( α 1 ) 2 g 2 ( x ) , ( 1 + g ( x ) ) α = ( 1 + g ( x ) ) ( 1 + g ( x ) ) α 1 ( 1 + g ( x ) ) ( 1 + ( α 1 ) g ( x ) + ( α 1 ) ( α 2 ) 2 g 2 ( x ) ) .

When α [ 1 , 2 ] . We have

α ( α 1 ) ( α 2 ) ( 1 + θ g ( x ) ) α 3 6 g 3 ( x ) 0 .

Thus

( 1 + g ( x ) ) α 1 + α g ( x ) + α ( α 1 ) 2 g 2 ( x ) .

The proof of Lemma 4 is complete. □

Lemma 5Let p > 1 , 1 / p + 1 / q = 1 , n k 1 , and let [ x ] denote the greatest integer less than or equal to the real numberx. Then we have

W ( k , p ) q p 1 k 1 / q n = k [ 1 n 1 + 1 / q ( 1 + g r ( n ) ) [ p ] 1 × ( 1 + ( p [ p ] ) g r ( n ) + ( p [ p ] ) ( p [ p ] 1 ) 2 g r 2 ( n ) ) ] .

Proof By Lemma 1 and the identity p q = p + q , q ( p 1 ) = p , it follows that

W ( k , p ) = k 1 1 / p n = k 1 n p ( j = 1 n 1 j 1 / p ) p 1 k 1 1 / p n = k 1 n p ( p p 1 n 1 1 / p p p 1 + 1 2 + 1 2 n 1 / p + 1 12 p 1 12 p n 1 + 1 / p ) p 1 = k 1 / q n = k 1 n p ( q n 1 / q 6 p + 12 q 1 12 p + 1 2 n 1 / p 1 12 p n 1 + 1 / p ) p 1 = k 1 / q n = k 1 n p q p 1 n ( p 1 ) / q ( 1 6 p + 12 q 1 12 p q n 1 / q + 1 2 q n 1 12 p q n 2 ) p 1 = q p 1 k 1 / q n = k 1 n 1 + 1 / q ( 1 + g r ( n ) ) p 1 .

Combining Lemmas 3 and 4, we obtain

W ( k , p ) q p 1 k 1 / q n = k [ 1 n 1 + 1 / q ( 1 + g r ( n ) ) [ p ] 1 ( 1 + g r ( n ) ) p [ p ] ] q p 1 k 1 / q n = k [ 1 n 1 + 1 / q ( 1 + g r ( n ) ) [ p ] 1 × ( 1 + ( p [ p ] ) g r ( n ) + ( p [ p ] ) ( p [ p ] 1 ) 2 g r 2 ( n ) ) ] .

This completes the proof of Lemma 5. □

Lemma 6Let 1 / p + 1 / q = 1 , n k 1 . If p ( 1 , 2 ) , then

W ( k , p ) q p 1 k 1 / q n = k [ 1 n 1 + 1 / q ( 1 + g l ( n ) ) [ p ] × ( 1 + ( p [ p ] 1 ) g l ( n ) + ( p [ p ] 1 ) ( p [ p ] 2 ) 2 g l 2 ( n ) ) ] .

If p [ 2 , + ) , then

W ( k , p ) q p 1 k 1 / q n = k [ 1 n 1 + 1 / q ( 1 + g l ( n ) ) [ p ] 2 × ( 1 + ( p [ p ] + 1 ) g l ( n ) + ( p [ p ] + 1 ) ( p [ p ] ) 2 g l 2 ( n ) ) ] .

Proof Since p q = p + q , q ( p 1 ) = p , using Lemma 1 gives

W ( k , p ) = k 1 1 / p n = k 1 n p ( j = 1 n 1 j 1 / p ) p 1 k 1 1 / p n = k 1 n p ( p p 1 n 1 1 / p p p 1 + 1 2 + 1 2 n 1 / p ) p 1 = k 1 / q n = k 1 n p ( q n 1 / q p + 2 q 2 p + 1 2 n 1 / p ) p 1 = k 1 / q n = k 1 n p q p 1 n ( p 1 ) / q ( 1 p + 2 q 2 p q n 1 / q + 1 2 q n ) p 1 = q p 1 k 1 / q n = k 1 n 1 + 1 / q ( 1 + g l ( n ) ) p 1 .

When p ( 1 , 2 ) . From Lemmas 3 and 4, we have

W ( k , p ) q p 1 k 1 / q n = k 1 n 1 + 1 / q ( 1 + g l ( n ) ) [ p ] 1 ( 1 + g l ( n ) ) p [ p ] q p 1 k 1 / q n = k [ 1 n 1 + 1 / q ( 1 + g l ( n ) ) [ p ] × ( 1 + ( p [ p ] 1 ) g l ( n ) + ( p [ p ] 1 ) ( p [ p ] 2 ) 2 g l 2 ( n ) ) ] .

When p [ 2 , + ) . Using Lemmas 3 and 4, we obtain

W ( k , p ) q p 1 k 1 / q n = k 1 n 1 + 1 / q ( 1 + g l ( n ) ) [ p ] 2 ( 1 + g l ( n ) ) p [ p ] + 1 q p 1 k 1 / q n = k [ 1 n 1 + 1 / q ( 1 + g l ( n ) ) [ p ] 2 × ( 1 + ( p [ p ] + 1 ) g l ( n ) + ( p [ p ] + 1 ) ( p [ p ] ) 2 g l 2 ( n ) ) ] .

Lemma 6 is proved. □

Lemma 7 (see[3])

Let p > 1 , a n 0 ( n = 1 , 2 , ), 0 < n = 1 a n p < . Then

n = 1 ( 1 n k = 1 n a k ) p k = 1 [ k 1 1 / p n = k 1 n p ( j = 1 n 1 j 1 / p ) p 1 a k p ] = k = 1 W ( k , p ) a k p .

### 3 Main results

Theorem 1For an arbitrary natural numberk, the following inequality holds true:

W ( k , 5 / 4 ) < R 5 / 4 ( k ) ,

where

R 5 / 4 ( k ) = 5 1 / 4 ( 5 133 240 k 1 / 5 17 , 689 144 , 000 k 2 / 5 + 25 48 k 19 192 k 6 / 5 17 , 689 480 , 000 k 7 / 5 + 467 4 , 224 k 2 + 133 18 , 000 k 11 / 5 + 97 38 , 400 k 3 + 133 60 , 000 k 16 / 5 + 61 504 , 000 k 4 + 19 240 , 000 k 5 ) .

Proof

Using Lemma 5 gives

W ( k , 5 / 4 ) 5 1 / 4 k 1 / 5 n = k [ 1 n 6 / 5 ( 1 + 1 4 g r ( n ) 3 32 g r 2 ( n ) ) ] = 5 1 / 4 k 1 / 5 n = k r 5 / 4 ( n ) ,

where

r 5 / 4 ( n ) = 1 n 6 / 5 133 600 n 7 / 5 17 , 689 240 , 000 n 8 / 5 + 1 40 n 11 / 5 + 133 8 , 000 n 12 / 5 41 9 , 600 n 16 / 5 133 60 , 000 n 17 / 5 + 1 4 , 000 n 21 / 5 1 60 , 000 n 26 / 5 .

Hence

W ( k , 5 / 4 ) 5 1 / 4 k 1 / 5 n = k ( 1 n 6 / 5 133 600 n 7 / 5 17 , 689 240 , 000 n 8 / 5 + 1 40 n 11 / 5 + 133 8 , 000 n 12 / 5 41 9 , 600 n 16 / 5 133 60 , 000 n 17 / 5 + 1 4 , 000 n 21 / 5 1 60 , 000 n 26 / 5 ) .

Using Lemma 2 and taking p = 6 / 5 , 7 / 5 , 8 / 5 , 11 / 5 , 12 / 5 , 16 / 5 , 17 / 5 , 21 / 5 , 26 / 5 in the right-hand side of inequality (13), respectively, we get

n = k 1 n 6 / 5 < 5 k 1 / 5 + 1 2 k 6 / 5 + 1 10 k 11 / 5 , n = k 133 600 n 7 / 5 < 133 240 k 2 / 5 133 1 , 200 k 7 / 5 , , n = k 1 4 , 000 n 21 / 5 < 1 12 , 800 k 16 / 5 + 1 8 , 000 k 21 / 5 + 7 80 , 000 k 26 / 5 , n = k 1 60 , 000 n 26 / 5 < 1 252 , 000 k 21 / 5 1 120 , 000 k 26 / 5 .

Adding up the above inequalities, we obtain

W ( k , 5 / 4 ) < R 5 / 4 ( k ) .

Theorem 1 is proved. □

Theorem 2For an arbitrary natural numberk, the following inequality holds true:

W ( k , 5 / 4 ) > L 5 / 4 ( k ) ,

where

L 5 / 4 ( k ) = 5 1 / 4 ( 5 9 16 k 1 / 5 81 640 k 2 / 5 15 , 309 25 , 600 k 3 / 5 + 25 48 k 45 448 k 6 / 5 + 3 , 159 51 , 200 k 7 / 5 15 , 309 64 , 000 k 8 / 5 + 17 1 , 408 k 2 129 5 , 120 k 11 / 5 + 891 12 , 800 k 12 / 5 45 , 927 640 , 000 k 13 / 5 27 102 , 400 k 3 567 64 , 000 k 16 / 5 + 1 12 , 800 k 4 3 , 213 640 , 000 k 21 / 5 ) .

Proof

Utilizing Lemma 6 gives

W ( k , 5 / 4 ) 5 1 / 4 k 1 / 5 n = k [ 1 n 6 / 5 ( 1 + g l ( n ) ) ( 1 3 4 g l ( n ) + 21 32 g l 2 ( n ) ) ] = 5 1 / 4 k 1 / 5 n = k l 5 / 4 ( n ) ,

where

l 5 / 4 ( n ) = 1 n 6 / 5 9 40 n 7 / 5 243 3 , 200 n 8 / 5 15 , 309 32 , 000 n 9 / 5 + 1 40 n 11 / 5 + 27 1 , 600 n 12 / 5 + 5 , 103 32 , 000 n 13 / 5 3 3 , 200 n 16 / 5 567 32 , 000 n 17 / 5 + 21 32 , 000 n 21 / 5 .

Hence

W ( k , 5 / 4 ) 5 1 / 4 k 1 / 5 n = k ( 1 n 6 / 5 9 40 n 7 / 5 243 3 , 200 n 8 / 5 15 , 309 32 , 000 n 9 / 5 + 1 40 n 11 / 5 + 27 1 , 600 n 12 / 5 + 5 , 103 32 , 000 n 13 / 5 3 3 , 200 n 16 / 5 567 32 , 000 n 17 / 5 + 21 32 , 000 n 21 / 5 ) .

Using Lemma 2 and taking p = 6 / 5 , 7 / 5 , 8 / 5 , 9 / 5 , 11 / 5 , 12 / 5 , 13 / 5 , 16 / 5 , 17 / 5 , 21 / 5 in the left-hand side of inequality (13), respectively, we get

n = k 1 n 6 / 5 > 5 k 1 / 5 + 1 2 k 6 / 5 , n = k 9 40 n 7 / 5 > 9 16 k 2 / 5 9 80 k 7 / 5 21 800 k 12 / 5 , , n = k 567 32 , 000 n 17 / 5 > 189 25 , 600 k 12 / 5 567 64 , 000 k 17 / 5 3 , 213 640 , 000 k 22 / 5 , n = k 21 32 , 000 n 21 / 5 > 21 102 , 400 k 16 / 5 + 21 64 , 000 k 21 / 5 .

Adding up the above inequalities, we obtain

W ( k , 5 / 4 ) > L 5 / 4 ( k ) .

Theorem 2 is proved. □

Theorem 3Let a n 0 ( n = 1 , 2 , ), 0 < n = 1 a n 5 / 4 < . Then

n = 1 ( 1 n k = 1 n a k ) 5 / 4 5 5 / 4 n = 1 ( 1 1 10 1 n 1 / 5 + η 5 / 4 ) a n 5 / 4 , (14)

where η 5 / 4 = 5 5 / 4 10 [ 5 5 / 4 W ( 1 , 5 / 4 ) ] 1 = 0.46 is the best possible under the weight coefficient W ( k , 5 / 4 ) .

Proof

By Lemma 7, we have

n = 1 ( 1 n k = 1 n a k ) 5 / 4 k = 1 W ( k , 5 / 4 ) a k 5 / 4 .

Therefore, to prove inequality (14), it suffices to show that

W ( k , 5 / 4 ) 5 5 / 4 ( 1 1 10 1 k 1 / 5 + η 5 / 4 ) . (15)

Obviously, inequality (15) becomes an equality for k = 1 . In what follows, we will assume that k 2 .

By Theorem 1 W ( k , 5 / 4 ) < R 5 / 4 ( k ) , we need only to prove that

R 5 / 4 ( k ) 5 5 / 4 ( 1 1 10 1 k 1 / 5 + η 5 / 4 ) .

Note that

η 5 / 4 = 5 5 / 4 10 [ 5 5 / 4 W ( 1 , 5 / 4 ) ] 1 = 0.44 > 11 25 ,

it suffices to show

R 5 / 4 ( k ) 5 5 / 4 ( 1 1 10 1 k 1 / 5 + 11 / 25 ) . (16)

Substituting k = x 5 in (16), inequality (16) becomes

R 5 / 4 ( x 5 ) 5 5 / 4 ( 1 1 10 1 x + 11 / 25 ) , where  x 2 5 ,

which is equivalent to the following inequality:

5 1 / 4 ( 5 133 240 x 17 , 689 144 , 000 x 2 + 25 48 x 5 19 192 x 6 17 , 689 480 , 000 x 7 + 467 4 , 224 x 10 + 133 18 , 000 x 11 + 97 38 , 400 x 15 + 133 60 , 000 x 16 + 61 504 , 000 x 20 + 19 240 , 000 x 25 ) 5 5 / 4 ( 1 1 10 1 x + 11 / 25 ) 5 133 240 x 17 , 689 144 , 000 x 2 + 25 48 x 5 19 192 x 6 17 , 689 480 , 000 x 7 + 467 4 , 224 x 10 + 133 18 , 000 x 11 + 97 38 , 400 x 15 + 133 60 , 000 x 16 + 61 504 , 000 x 20 + 19 240 , 000 x 25 5 1 2 1 x + 11 / 25 133 240 x 17 , 689 144 , 000 x 2 + 25 48 x 5 19 192 x 6 17 , 689 480 , 000 x 7 + 467 4 , 224 x 10 + 133 18 , 000 x 11 + 97 38 , 400 x 15 + 133 60 , 000 x 16 + 61 504 , 000 x 20 + 19 240 , 000 x 25 + 1 2 1 x + 11 / 25 0 f ( x ) 221 , 760 , 000 x 25 ( 25 x + 11 ) 0 , (17)

where

f ( x ) = 300 , 300 , 000 x 25 + 2 , 032 , 838 , 500 x 24 + 299 , 651 , 660 x 23 2 , 887 , 500 , 000 x 21 721 , 875 , 000 x 20 + 445 , 702 , 950 x 19 + 89 , 895 , 498 x 18 612 , 937 , 500 x 16 310 , 656 , 500 x 15 18 , 024 , 160 x 14 14 , 004 , 375 x 11 18 , 451 , 125 x 10 5 , 407 , 248 x 9 671 , 000 x 6 295 , 240 x 5 438 , 900 x 193 , 116 .

From the hypothesis x 2 5 > 1.14 , we have

300 , 300 , 000 x 25 + 2 , 032 , 838 , 500 x 24 + 299 , 651 , 660 x 23 2 , 887 , 500 , 000 x 21 721 , 875 , 000 x 20 + 445 , 702 , 950 x 19 + 89 , 895 , 498 x 18 > ( 300 , 300 , 000 × 1.14 4 + 2 , 032 , 838 , 500 × 1.14 3 + 299 , 651 , 660 × 1.14 2 2 , 887 , 500 , 000 ) x 21 721 , 875 , 000 x 20 + 445 , 702 , 950 x 19 + 89 , 895 , 498 x 18 = 1 , 020 , 861 , 716 x 21 721 , 875 , 000 x 20 + 445 , 702 , 950 x 19 + 89 , 895 , 498 x 18 = [ ( 1 , 020 , 861 , 716 x 721 , 875 , 000 ) x 2 + 445 , 702 , 950 x + 89 , 895 , 498 ] x 18 > [ ( 1 , 020 , 861 , 716 × 1.14 721 , 875 , 000 ) × 1.14 2 + 445 , 702 , 950 × 1.14 + 89 , 895 , 498 ] x 18 = 1 , 172 , 299 , 661 x 18 .

Further, we have

f ( x ) > 1 , 172 , 299 , 661 x 18 612 , 937 , 500 x 16 310 , 656 , 500 x 15 18 , 024 , 160 x 14 14 , 004 , 375 x 11 18 , 451 , 125 x 10 5 , 407 , 248 x 9 671 , 000 x 6 295 , 240 x 5 438 , 900 x 193 , 116 > 1 , 172 , 299 , 661 x 18 612 , 937 , 500 x 18 310 , 656 , 500 x 18 18 , 024 , 160 x 18 14 , 004 , 375 x 18 18 , 451 , 125 x 18 5 , 407 , 248 x 18 671 , 000 x 18 295 , 240 x 18 438 , 900 x 18 193 , 116 x 18 = 191 , 220 , 497 x 18 > 0 .

Consequently, inequality (17) holds true, and inequality (14) is proved.

Let us now show that η 5 / 4 = 5 5 / 4 10 [ 5 5 / 4 W ( 1 , 5 / 4 ) ] 1 = 0.46 is the best possible under the weight coefficient W ( k , 5 / 4 ) .

Consider inequality (14) in a general form as

W ( k , 5 / 4 ) 5 5 / 4 ( 1 1 10 1 k 1 / 5 + η 5 / 4 ) . (18)

Putting k = 1 in (18) yields

η 5 / 4 5 5 / 4 10 [ 5 5 / 4 W ( 1 , 5 / 4 ) ] .

Thus the best possible value for η 5 / 4 in (18) should be η min = 5 5 / 4 10 [ 5 5 / 4 W ( 1 , 5 / 4 ) ] .

This completes the proof of Theorem 3. □

Remark 1 From the definition of W ( k , p ) and in the same way as in [17], we can establish the following accurate estimates of W ( 1 , 5 / 4 ) :

6.965042829 < W ( 1 , 5 / 4 ) < 6.967740323 . (19)

Further, the approximation of η 5 / 4 can be derived as follows:

η 5 / 4 = 5 5 / 4 10 [ 5 5 / 4 W ( 1 , 5 / 4 ) ] 1 = 0.46 .

Remark 2 For p = 5 / 4 , inequality (11) can be written as

n = 1 ( 1 n k = 1 n a k ) 5 / 4 5 5 / 4 n = 1 ( 1 1 ( 1 5 ) 5 / 4 W ( 1 , 5 / 4 ) n 1 / 5 ) a n 5 / 4 . (20)

It is easy to observe that

1 10 1 n 1 / 5 + η 5 / 4 > 1 10 1 n 1 / 5 + 4 , 711 / 10 , 000 > 7 100 n 1 / 5

and

1 ( 1 5 ) 5 / 4 W ( 1 , 5 / 4 ) < 1 ( 1 5 ) 5 / 4 × 6.967740323 = 0.06808 < 7 100 ,

hence

1 ( 1 5 ) 5 / 4 W ( 1 , 5 / 4 ) n 1 / 5 < 1 10 1 n 1 / 5 + η 5 / 4 .

This implies that inequality (14) is stronger than inequality (11).

### Competing interests

The authors declare that they have no competing interests.

### Authors’ contributions

YD finished the proof and the writing work. SW gave YD some advice on the proof and writing. DH gave YD lots of help in revising the paper. All authors read and approved the final manuscript.

### Acknowledgements

The present investigation was supported, in part, by the Natural Science Foundation of Fujian province of China under Grant 2012J01014 and, in part, by the Foundation of Scientific Research Project of Fujian Province Education Department of China under Grant JK2012049.

### References

1. Hardy, GH, Littlewood, JE, Pólya, G: Inequalities, Cambridge University Press, Cambridge (1952)

2. Mitrinović, DS, Pečarić, JE, Fink, AM: Inequalities Involving Functions and Thier Integrals and Derivatives, Kluwer Academic, Dordrecht (1991)

3. Yang, BC, Zhu, YH: An improvement on Hardy’s inequality. Acta Sci. Natur. Univ. Sunyatseni. 37(1), 41–44 (1998)

4. Huang, QL: An improvement of series Hardy’s inequality for p = 3 . J. Hubei Inst. Natl.. 17(3), 54–57 (1999)

5. Huang, QL: A sharpness and improvement of Hardy’s inequality for p = 3 / 2 . J. Guangxi Norm. Univ. (Nat. Sci. Ed.). 18(1), 38–41 (2000)

6. Huang, QL: An improvement of Hardy’s inequality in an interval. Acta Sci. Natur. Univ. Sunyatseni. 39(3), 20–24 (2000)

7. Huang, QL: An improvement of Hardy’s series inequality in the interval [ 2 , 5 ] . J. South China Univ. Technol. (Natl. Sci. Ed.). 28(2), 64–68 (2000)

8. Huang, QL: An extension of a strengthened inequality. J. Guangdong Educ. Inst.. 21(2), 17–20 (2001)

9. Yang, BC: On a strengthened version of Hardys inequality. J. Guangdong Educ. Inst.. 25(5), 5–8 (2005)

10. Kuang, JC: Applied Inequalities,p. 576. Shangdong Science and Technology Press, Jinan (2010)

11. Zhang, XM: A new proof method of analytic inequality. RGMIA Research Report Collection. 12(1), 18–29 (2009)

12. Zhang, XM, Chu, YM: New Discussion to Analytic Inequalities, pp. 260–275. Harbin Institute of Technology press, Harbin (2009)

13. Zhang, XM, Chu, YM: A new method to study analytic inequalities. J. Inequal. Appl. (2010). http://www.hindawi.com/journals/jia/2010/698012

14. Yang, L, Xia, BC: Automated Discovering and Proving for Mathematical Inequalities, pp. 33–42. Science Press, Beijing (2008)

15. Yang, L, Zhang, JZ, Hou, XR: Nonlinear Algebraic Equation Systems and Automated Theorem Proving, pp. 137–166. Shanghai Science’s and Technology’s Education Publishing House, Shanghai (1996)

16. He, D: The automatic verification of Hardy inequality’s improvements and its improving type of P N . J. Guangdong Educ. Inst.. 32(3), 28–35 (2012)

17. Deng, YP, He, D, Wu, SH: A sharpened version of Hardy’s inequality and the automated verification program. J. Math. Pract. Theory (2012, submitted)

18. Huang, YZ, He, D: An improvement of Hardy’s inequality for p = 3 / 2 . J. Shantou Univ. (Natl. Sci. Ed.). 27(3), 15–22 (2012)

19. Yang, BC: On a strengthened Hardy’s inequality. J. Xinyang Teach. Coll. (Natl. Sci. Ed.). 15(1), 37–39 (2002)

20. Huang, QL: A strengthened Hardy’s inequality in the interval [ 1 , 2 ] . J. Guangdong Educ. Inst.. 22(2), 20–23 (2002)

21. Huang, QL, Yang, BC: A strengthened dual form of Hardy’s inequality. J. Math. (PRC). 25(3), 307–311 (2005)

22. Zhu, YH, Yang, BC: Improvement on Euler’s summation formula and some inequalities on sums of powers. Acta Sci. Natur. Univ. Sunyatseni. 36(4), 21–26 (1997)

23. Qian, X, Meixiu, Z, Zhang, X: On a strengthened version of Hardy’s inequality. J. Inequal. Appl.. 2012, 300 (2012). BioMed Central Full Text